(untitled) (Jurnal Wahana Konseling, 2024)
The purpose of this study was to determine the effectiveness of group counseling services self-management techniques to reduce the intensity of smartphone use. This type of research is an experimental research with a one group pretest-posttest design. The research sampling technique used purposive sampling with 6 students. Based on the paired test results, the t test sample showed the results that t-count (6.564) ≥ t-table (2.015), this shows that group counseling services, self-management techniques have proven effective in reducing the intensity of smartphone use in students. Furthermore, for teacher recommendations, guidance and counseling, schools can implement and develop group counseling, self-management techniques as an alternative strategy to reduce the intensity of smartphone use.